2018
DOI: 10.6018/eglobal.18.1.322641
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre olor y aislamiento social en pacientes con heridas tumorales malignas: estudio piloto

Abstract: Objetivo: Identificar as associações entre odor e isolamento social em pacientes com feridas tumorais malignas. Material e método: Estudo piloto com corte transversal realizado com nove pacientes com feridas tumorais malignas atendidos em um hospital universitário no período de 2014 a 2016. Coletaram-se dados por meio de aplicação de escala likert de cinco pontos para avaliação do isolamento social relacionado ao odor de feridas tumorais malignas, durante as consultas de enfermagem. Analisaram-se os dados por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…[14][15][16] Correlational tended to focus on relationships between symptoms and health-related quality of life. 8,14,17 Randomized clinical trials or nonrandomized comparison cohort study designs tended to evaluate the efficacy of topical agents and dressings on odor in patients with MFWs. [18][19][20] Details of included studies are shown in Table 4.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Correlational tended to focus on relationships between symptoms and health-related quality of life. 8,14,17 Randomized clinical trials or nonrandomized comparison cohort study designs tended to evaluate the efficacy of topical agents and dressings on odor in patients with MFWs. [18][19][20] Details of included studies are shown in Table 4.…”
Section: Search Strategymentioning
confidence: 99%
“…1,5,6 Patients with MFW experience psychosocial distress, including feelings of social isolation, loneliness, and living alone. 7,8 Wound management associated with psychosocial symptoms also influences the quality of life in these patients. 9 The complex nature and terminal prognosis of MFWs require a comprehensive, holistic nursing approach to meet patients' biological/physical, psychological, social, and spiritual needs.…”
Section: Introductionmentioning
confidence: 99%
“…O olhar sobre essas lesões volta-se ao controle de sintomas, buscando conforto e qualidade de vida. O agravamento do quadro clinico do paciente, favorece a deterioração progressiva da ferida, e em consequência disso, os sintomas podem ser de difícil controle, tais como, o odor, elevados níveis de exsudado, dor e hemorragia (Ferreira Junior;Polakiewicz;Fuly, 2019). Dentre essas lesões temos: ferida tumoral, lesões por pressão e úlcera terminal de Kennedy, as quais foram abordadas neste estudo.…”
Section: Características Das Lesões E Produtos Utilizados Para Controle De Sintomasunclassified
“…Além de uso de curativos com carvão ativado, uma adequada oclusão da ferida e a adoção de medidas para amenizar o odor no ambiente, como o uso de aromas dentre outras. Entretanto, o uso de hidrocolóides e os alginatos podem levar a produção de odor (Santos et al, 2019).…”
Section: Características Das Lesões E Produtos Utilizados Para Controle De Sintomasunclassified
See 1 more Smart Citation